Abiotrophia defectiva Infective Endocarditis: A Rare and Dangerous Cause of Endocarditis. (8th March 2022) - Lancaster, Ian; Patel, Deep; Tamboli, Cyrus; Chun, Patricia; Sethi, Vikas; Namey, Joseph
Abstract : Infective endocarditis is an uncommon heart infection, typically involving heart valves. Abiotrophia defectiva is a rare cause of endocarditis, typically found within the GI tract, and is usually difficult to isolate and requires specialized media. We report a case of Abiotrophia defectiva endocarditis following a root canal.